Antiretroviral activity of 5-azacytidine during treatment of a HTLV-1 positive myelodysplastic syndrome with autoimmune manifestations - Diamantopoulos Panagiotis T; Michael Maria; Benopoulou Olga; Bazanis Efthymia; Tzeletas George; Meletis John; Vayopoulos George; Viniou Nora-Athina (Virology Journal, 2012)
Abstract Myelodysplastic syndromes (MDS) are often accompanied by autoimmune phenomena. The underlying mechanisms for these associations remain uncertain, although T cell activation seems to be important. Human T-lymphotropic virus (HTLV-1) has been detected in patients with myelodysplastic syndromes, mostly in regions of the world which are endemic for the virus, and where association of HTLV-1 with rheumatological manifestation is not rare. We present here the case of a 58 year old man who presented with cytopenias, leukocytoclastic vasculitis of the skin and glomerulopathy, and was diagnosed as MDS (refractory anemia with excess blasts - RAEB 1). The patient also tested positive for HTLV-1 by PCR. After 8 monthly cycles of 5-azacytidine he achieved a complete hematologic remission. Following treatment, a second PCR for HTLV-1 was carried out and found to be negative. This is the first report in the literature of a HTLV-1-positive MDS with severe autoimmune manifestations, which was treated with the hypomethylating factor 5-azacitidine, achieving cytogenetic remission with concomitant resolution of the autoimmune manifestations, as well as HTLV-1-PCR negativity. HTLV-1-PCR negativity may be due to either immune mediated clearance of the virus, or a potential antiretroviral effect of 5-azacytidine. 5-azacytidine is known for its antiretroviral effects, although there is no proof of its activity against HTLV-1 infection in vivo.